ANALISIS DESKRIPTIF RENDAHNYA HASIL BELAJAR SEJARAH KELAS V SDN PANANCANGAN 4 KOTA SERANG - Khaeroni, Khaeroni; sari, Nurmala; Saefurohman, Asep (PD PGMI se Indonesia, 2020)
The purpose of this study is to duscribe the factors of the low of social science learning outcomes History subject in V class in SDN Panancangan 4 Kota Serang. The materials of this study is descriptive qualitative methods, the Data collectid by observation, interviews, documentation, and student learning outcomes. Students who have low learning outcomes on average as much as 92% of students with the types of difficulties include: lack of student understanding in historical material, student lack of active in asking, then students' inability to remember material such as (mentioning names, years of administration and inheritance), and inappropriate learning strategies. The results of the study shows that generally of the low social studies learning outcomes classified into two factors that is internal and external factors, namely the factors found in students such as psychological factors in learning, motivation and concentration of learning. In addition, there are factors that exist outside of the student's self or external factors, such as the quality of parentid advisionary learning outside of school. Although the learning outcomes obtained by students are more dependent on the students themselves, it is hoped that the instructors will play a role in enhancing them, namely directing students to be able to prepare themselves physically and mentally, increase student learning concentration, give students motivation to learn, teach them strategies - learning strategies, how to be able to learn according to each style, study thoroughly, and get used to sharing with each other.Â Keywords: Low student learning outcomes, Material history, Social Studie